The impact of environmental pollution on biodiversity in the Shatt al-Arab/southern Iraq: A review Article (The Peerian Journal, 2023)
Stalinization and the deterioration of the quality of the Shatt al-Arab water cause a state of severe water scarcity due to the water being unfit for drinking, whether for humans or animals, in addition to agriculture, which prompted many to migrate to these areas for fear for themselves and their livestock. Therefore, Iraqi experts and officials warned of an environmental catastrophe in Shatt al-Arab due to the significant increase in salinity, which has now exceeded uses for agricultural purposes, which led to the destruction of marine life. The environment of the Shatt al-Arab was good and suitable for many types of aquatic life, but it has become, like seawater coming from the Gulf, unsuitable for many types of marine life and fish which caused a severe shortage. Pollution in the Shatt al-Arab River comes as a result of the lack of fresh water supplies from the main sources of the rivers Tigris and Euphrates rivers, where the Shatt al-Arab represents the meeting point of these two rivers, in addition to cutting off the Karun River, which comes from Iran and feeds the southern part.